2009
DOI: 10.1190/1.3236371
|View full text |Cite
|
Sign up to set email alerts
|

Hydrocarbon prospects in the Western Black Sea of Ukraine

Abstract: Th is paper presents the author's integrated regional studies during the last decade. Th e main purpose is to present an overall understanding of the geological structure, sedimentary basins and hydrocarbon systems of the whole Western Black Sea Zone (WBSZ). Th is study is based on original data from boreholes, seismic and gravity-magnetic surveys and hydrocarbon accumulations.Many geophysical borehole data obtained for WBSZ during the last 3-4 decades were interpreted mostly at a national level using diff ere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0
6

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 0 publications
1
26
0
6
Order By: Relevance
“…[10] The major contraction taking place at the southern margin of the Black Sea led to the onset of inversion recorded in the extensional basins and to the formation of other foreland and thrust-sheet top basins [e.g., Finetti et al, 1988;Robinson et al, 1996;Sunal and Tüysüz, 2002;Nikishin et al, 2003]. In contrast with the large-scale structures observed in the south, inversion along the NE part of the Western Black Sea led to the formation of OligoceneMiocene reverse faults and associated folds with N-ward vergence and offsets in the order of tens to few hundreds of meters [Afanasenkov et al, 2007;Khriachtchevskaia et al, 2009]. Along this northern margin, the structural grain changes rapidly east of the Odessa-West Crimea fault system (Figure 1), where the Crimean Orogen is thrusted S-wards over the Black Sea domain from Oligocene to recent times [e.g., Stovba et al, 2009].…”
Section: Constraints On the Opening And Inversion Of The Western Blacmentioning
confidence: 99%
See 2 more Smart Citations
“…[10] The major contraction taking place at the southern margin of the Black Sea led to the onset of inversion recorded in the extensional basins and to the formation of other foreland and thrust-sheet top basins [e.g., Finetti et al, 1988;Robinson et al, 1996;Sunal and Tüysüz, 2002;Nikishin et al, 2003]. In contrast with the large-scale structures observed in the south, inversion along the NE part of the Western Black Sea led to the formation of OligoceneMiocene reverse faults and associated folds with N-ward vergence and offsets in the order of tens to few hundreds of meters [Afanasenkov et al, 2007;Khriachtchevskaia et al, 2009]. Along this northern margin, the structural grain changes rapidly east of the Odessa-West Crimea fault system (Figure 1), where the Crimean Orogen is thrusted S-wards over the Black Sea domain from Oligocene to recent times [e.g., Stovba et al, 2009].…”
Section: Constraints On the Opening And Inversion Of The Western Blacmentioning
confidence: 99%
“…The Odessa-West Crimean fault system has been defined on the basis of potential field geophysics, wells and older seismic reflection profiles to accommodate a dextral displacement of the Odessa Shelf units, such as the Karkinit Trough, the Shtormavaya Graben and the Kalamit Ridge (Figure 1) [e.g., Garkalenko, 1970;Tugolesov et al, 1985;Robinson et al, 1996] (or their counterparts in Romanian nomenclature [see Dinu et al, 2005]), when compared with their equivalent units located in Crimea and East Black Sea Basin. More recent interpretations have demonstrated that this dextral structure is characterized in seismic lines by a large zone of deformation made up by high-angle reverse faults with small vertical offsets [Afanasenkov et al, 2007;Khriachtchevskaia et al, 2009].…”
Section: Constraints On the Opening And Inversion Of The Western Blacmentioning
confidence: 99%
See 1 more Smart Citation
“…Seismic data from the Black Sea are briefly presented in this paper because the most essential results are described in full detail by [Starostenko et al, 2004a,b]. Here results are updated because new seismic information has been obtained since that time [Slishinsky et al, 2007;Khriachtchevskaia et al, 2009;Scott et al, 2009;Scott, 2009;Yegorova et al, , 2013Piip, Ermakov, 2011;Stovba et al, 2013;Graham et al, 2013]. All these data were used to constrain parameters of the sedimentary cover in gravity modeling.…”
Section: Introductionmentioning
confidence: 99%
“…In the deep-water part magnetic susceptibility information is not available. In another way, values of magnetic susceptibility of samples can be used from the adjacent onshore because marine seismic stratigraphy is similar to that exposed on land [see for example, Rangin et al, 2002;Khriachtchevskaia et al, 2009;Hippolyte et al, 2010;Georgiev, 2012]. They do not exceed mostly (30-40) 10 5 SI on the conjugate margins of the Black Sea in the Pon and Cr [Kaymakci et al, 2003;Guzhikov et al, 2012].…”
Section: Introductionmentioning
confidence: 99%